The role of community participation in planning the delivery of clean water to rural communities : a case study of Jeppe's Reef - Thwala, Wellington Didibhuku (My University, 1998)
Water is a human right and to save water is a human responsibility, Despite tile very basic need for water, not everyone has access to it However, access to an adequate supply of water, defined in terms of water quality, quantity and distance to the supply, is denied to millions of rural people in the developing countries. The ambitious goal manifested in the International Drinking Water and Water Supply and Sanitation Decade (IDWSSD) was that by 1990, all the inhabitants of the world would have access to safe drinking water. This goal has clearly not been achieved, and certainly not in South Africa. In South Africa more than 12 million people do not have access to clean water and less than half of the rural population has a safe and accessible water supply. Communities have had little say in the provision of water and decision-making in the water delivery, agencies has reflected broader apartheid ideology. The study attempts to investigative the problems which are faced by rural communities that hinder participation in the delivery of clean water supply. The study concentrate on aspects such as what is participation, the importance of the community in decision making, who should participate, how to ensure participation, and the role of the planner. It proposes the importance of involving communities in the planning for the delivery of clean water supply to rural communities. Emphasis is on enhancing the role of community participation in planning and implementing rural water projects. Jeppe's Reef is the case study of this discourse. In the final analysis it was discovered there is a great need for involving the community in water project decision-making.
A DISSERTATION SUBMITTED TO THE DEPARTMENT OF TOWN AND REGIONAL PLANNING, UNIVERSITY OF THE WITWATERSRAND, JOHANNESBURG, IN PARTIAL FULFILMENT OF THE REQUIREMENTS FOR THE DEGREE OF Msc DEVELOPMENT PLANNING.
Keywords: Community development -- South Africa -- Case studies.; Water supply, Rural -- South Africa -- Citizen participation.